Visual control of posture in real and virtual environments - Kelly, J. W.; Riecke, Bernhard E.; Loomis, J. M.; Beall, A. C. (Perception & Psychophysics, 2008)
In two experiments, we investigated the stabilizing influence of vision on human upright posture in real and virtual environments. Visual stabilization was assessed by comparing eyes-open with eyes-closed conditions while participants attempted to maintain balance in the presence of a stable visual scene. Visual stabilization in the virtual display was reduced, as compared with real-world viewing. This difference was partially accounted for by the reduced field of view in the virtual display. When the retinal flow in the virtual display was removed by using dynamic random-dot stereograms with single-frame lifetimes (cyclopean stimuli), vision did not stabilize posture. There was also an overall larger stabilizing influence of vision when more unstable stances were adopted (e.g., one-foot, as compared with side-by-side, stance). Reducing the graphics latency of the virtual display by 63% did not increase visual stabilization in the virtual display. Other visual and psychological differences between real and virtual environments are discussed.
Keywords: Riecke; Riecke_2008; bernhard-riecke; distance; egocentric; iSpaceWeb; journalPaper